Survey Investigation Design (SID) Pintu Air Rejomulyo - Susilo, Hendro (LPPM Universitas Merdeka Madiun, 2020)
Abstract— In connection with efforts to control flooding problems in the Jeroan River, Teratai River, Sono River, and Maling River, in Madiun is necessary to conduct a survey and investigation. One of the recommendations in the work was the need for flood control with the Rejomulyo sluice gate. So that the Study of Investigation Design (SID) of the Rejomulyo sluice can provide a description of the benefits of the sluice gates. The geometry of the river flow in the Sono River in the existing condition with flood design Q1.05th occurred flooding at elevation +63.64 to elevation +66.23, in the existing condition with flood design Q2th there was a flood at +64.56 to elevation +67.65. Whereas the river flow geometry in the Sono River in conditions with the presence of sluice gates and retarding basin with flood design Q2th occurred at an elevation of +63.90 to elevation +67.12. The use of retention reservoirs in the study area was effective enough to be able to cut flood peaks from 175 m3/s to 117 m3/s (2 year return period). while for annual returns, it can cut flood peaks from 70 m3/s to 48 m3/s. so the cutting ability of the peak of the flood is 30%. The duration of the peak cutting of the flood runs for 5-7 hours during the flood period. Keywords—: sluice gate; survey investigation design; flood.